(untitled) (Communications in Computational Physics, 2010)
It is known that the submerged seamount/ridge is a source for the generation of internal tides. In this paper, a three-dimensional two-layer model is set up to study the generation of internal tides by tidal flows over a submerged seamount/ridge in the channel. Several numerical experiments with different topographic features, upper layer depths, tidal flows and background currents are carried out to study the variations of the induced internal tides. It is shown that, for the specific stratification, the seamount feature, the slope, the initial upper layer depth and the imposing driven force determine the Froude number near the seamount peak. Once when the Froude number is supercritical, the associated maximum amplitude of the induced internal tide is so large that the internal tide begins to disintegrate, which brings about severe variations of the current velocity and the water elevation fields, and the associated induced baroclinic tidal energy around the seamount peak is much larger than the barotropic one. The Richardson number greater than 1/4 is a criterion for stability of shear flow. Since the maximum tidal velocity changes within 0 ∼ 360◦ with time in a period around the seamount peak, the induced internal tide does not stride the seamount peak before it disintegrates, which is different from the two-dimensional modeled results. The asymmetrical slope of the submerged seamount is a mechanism for the asymmetrical internal tide generation.